Stories from the benthos: decolonizing ecological baselines for understanding social-ecological resilience - Ortenzi, Kate; Jacque, James; Saunders, Michelle; Schmidt, Jörn Oliver; Bailey, Megan (Frontiers in Climate, 2025)
The people of Nunatsiavut and the Government of Canada have a modern-day treaty that recognizes Labrador Inuit sovereignty on their land and throughout their coastal waters. Together, the Nunatsiavut and Canadian governments outlined the most important research priorities for Nunatsiavut's marine space, which includes setting ecological baselines of the benthos and better understanding Inuit use of benthic resources. This study responds to that priority to understand the social, cultural, and ecological roles benthic species play throughout Nunatsiavut using methodologies that align with Inuit cosmology and concepts of relationality. In doing so, this work attempts to decolonize the process of establishing ecological baselines in Indigenous territories. By conducting semi-structured interviews and adapting network analysis, we show how benthic species are related to each other through the lens of Labrador Inuit knowledge and experience. Labrador Inuit speak of the relationships between the benthos and fish, marine mammals, birds, and terrestrial plants—diminishing the arbitrary boundaries between land and sea to better reflect Inuit worldview. Results also demonstrate how benthic species are integrated into activities such as commercial and subsistence fishing, hunting, play, research, gardening, crafting, ceremony, medicine, and sled dog care. By establishing baselines in this decolonized manner, they contribute to understanding the profound social-ecological effects of climate change that go well beyond the direct and indirect results of changes in species presence, absence, and abundance. Most importantly, however, is the understanding of the complexity of benthic relationships for Labrador Inuit, which supports resilience in the face of climatic change.